Introduction to the 2024 Election Outreach to Raise Awareness of Voting Rights Among the Elderly - Sri Fitri Fitriani; I Gede Agus Kurniawan (Universitas Lambung Mangkurat, 2024)
This socialization aims to increase the knowledge and awareness of voting rights among the elderly at PSTW Wana Seraya Denpasar. Enhancing voter participation is crucial for the success of elections. However, ironically, the elderly often get overlooked in election socialization and education, leading to low voter turnout. The community service activity at PSTW Wana Seraya was conducted through an election socialization and education program utilizing the Participatory Action Research (PAR) method in a sharing session. Topics discussed included exercising voting rights, properly using the ballot and the dangers of abstaining from voting. This community service, conducted using the sharing session method, has increased voters' knowledge and awareness of voting rights. This is evidenced by the enthusiasm of the elderly in asking and answering questions and the positive feedback in participating in the socialization program.